1998
DOI: 10.1097/00004647-199802000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Redox Control of Neuronal Damage during Brain Ischemia after Middle Cerebral Artery Occlusion in the Rat: Immunohistochemical and Hybridization Studies of Thioredoxin

Abstract: Thioredoxin (TRX) is a small, multifunctional protein with a redox-active site and multiple biological functions that include reducing activity for reactive oxygen intermediates. We assayed TRX and TRX mRNA by immunohistochemical methods and hybridization experiments in the rat brain after middle cerebral artery (MCA) occlusion. During ischemia, the immunoreactivity for TRX decreased; it disappeared after MCA occlusion in the ischemic regions. It rapidly decreased and nearly disappeared at 4 and 16 hours after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 51 publications
1
44
0
Order By: Relevance
“…We have reported the proliferated astroglial induction of TRX in the CA1 region during transient forebrain ischemia (33). Recently we documented decreased TRX in the ischemic core and increased TRX in the penumbral ischemic region during permanent middle cerebral artery occlusion in rats (34). In combination, these findings indicate that TRX and the redox system modulated by TRX has a function in the cellular defense against oxidative stress in neurons as well as in other cell types and may play a role during brain injury.…”
Section: Discussionmentioning
confidence: 88%
“…We have reported the proliferated astroglial induction of TRX in the CA1 region during transient forebrain ischemia (33). Recently we documented decreased TRX in the ischemic core and increased TRX in the penumbral ischemic region during permanent middle cerebral artery occlusion in rats (34). In combination, these findings indicate that TRX and the redox system modulated by TRX has a function in the cellular defense against oxidative stress in neurons as well as in other cell types and may play a role during brain injury.…”
Section: Discussionmentioning
confidence: 88%
“…Several studies, for example, have already reported that injection of a bolus of Trx substantially prevents ischemic reperfusion injury (15)(16)(17)(18). These findings were previously ascribed to the reducing power of Trx and its ability to remove locally generated reactive oxygen intermediates.…”
Section: Discussionmentioning
confidence: 97%
“…It is induced by oxidative stress (8,11), is translocated into the nucleus in stressed cells (8,11), is chemotactic in vitro for eosinophils (7), and effectively blocks ischemic injury (15)(16)(17)(18). In addition, our recent studies show that Trx has potent in vitro and in vivo chemoattractant activity for murine neutrophils, monocytes, and lymphocytes (9).…”
mentioning
confidence: 99%
“…Hypobaric hypoxia-induced preconditioning increased Trx-2 mRNA expression in the rat brain (355); the same procedure also markedly strengthened the increased levels of Trx-1 and Trx-2 produced by a subsequent, severe hypobaric hypoxia (395,396). It is also pertinent to mention that in rats subjected to MCAO, both Trx mRNA expression and protein levels rapidly decreased in the ischemic core (i.e., striatum and frontoparietal cortex), but increased in perifocal regions throughout the 4-to 24-h period after MCAO (403).…”
Section: Sod2mentioning
confidence: 99%